The Destruction of the Canaanites: God, Genocide, and Biblical Interpretation. By Charlie Trimm - Day, Jack A. (The journal of theological studies, 2025)
This volume is a concise introduction to an infamous issue in Old Testament ethics: the divinely mandated mass killing of the Canaanites. Charlie Trimm con